1997
DOI: 10.1023/a:1018392603062
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Allozyme variation at 35 gene loci is investigated in 161 specimens of the uniparental Caucasian lizard Lacerta dahli from several locations in Armenia and Georgia. All individuals are heterozygotic at 12 loci, and homozygotic at 21 loci. Variation at two loci results in five uniparental clones. One clone is widespread whereas four are geographically restricted and are represented by only one or two individuals. Because successful formation of uniparental clones is rare, and because the biparental species form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Previously, an allozyme analysis conducted at 35 gene loci in three Armenian and three Georgian sampled populations of D. dahli revealed one major widespread clone and four rare clones detected only in restricted populations [18]. The authors concluded that the observed allozyme pattern in D. dahli generally followed Parker et al .’s model [10], which is consistent with its single hybridization origin.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Previously, an allozyme analysis conducted at 35 gene loci in three Armenian and three Georgian sampled populations of D. dahli revealed one major widespread clone and four rare clones detected only in restricted populations [18]. The authors concluded that the observed allozyme pattern in D. dahli generally followed Parker et al .’s model [10], which is consistent with its single hybridization origin.…”
Section: Discussionmentioning
confidence: 91%
“…The authors concluded that the observed allozyme pattern in D. dahli generally followed Parker et al .’s model [10], which is consistent with its single hybridization origin. Nevertheless, they noted that possible multiple origins for D. dahli should be investigated further using more effective genomic markers [18]. Among parthenogenetic Darevskia , D. rostombekovi was also suggested to be of single origin [32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations